2005
DOI: 10.1021/jm050235r
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptides as Effective Prodrugs of the Unnatural Amino Acid (+)-2-Aminobicyclo[3.1.0]hexane-2,6-dicarboxylic Acid (LY354740), a Selective Group II Metabotropic Glutamate Receptor Agonist

Abstract: (+)-2-Aminobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (1), also known as LY354740, is a highly potent and selective agonist for group II metabotropic glutamate receptors (mGlu receptors 2 and 3) tested in clinical trials. It has been shown to block anxiety in the fear-potentiated startle model. Its relatively low bioavailability in different animal species drove the need for an effective prodrug form that would produce a therapeutic response at lower doses for the treatment of anxiety disorders. We have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…There were no reports of convulsions or other neurobehavioral adverse events. Plasma concentrations of LY354740 were comparable to those previously associated with efficacy in GAD (data on file, Eli Lilly and Co.), confirming the utility of using a dipeptide analog to increase the oral bioavailability (by way of peptide transporters) of otherwise poorly absorbed amino-acid analogs such as LY354740 (Bueno et al, 2005;Rorick-Kehn et al, 2006). The use of the prodrug LY544344 is associated with increased oral bioavailability and decreased variability of active moiety (LY354740) in plasma concentration.…”
Section: Ly354740 Plasma Concentrationssupporting
confidence: 68%
See 1 more Smart Citation
“…There were no reports of convulsions or other neurobehavioral adverse events. Plasma concentrations of LY354740 were comparable to those previously associated with efficacy in GAD (data on file, Eli Lilly and Co.), confirming the utility of using a dipeptide analog to increase the oral bioavailability (by way of peptide transporters) of otherwise poorly absorbed amino-acid analogs such as LY354740 (Bueno et al, 2005;Rorick-Kehn et al, 2006). The use of the prodrug LY544344 is associated with increased oral bioavailability and decreased variability of active moiety (LY354740) in plasma concentration.…”
Section: Ly354740 Plasma Concentrationssupporting
confidence: 68%
“…To improve LY354740 absorption and further assess the therapeutic effects of mGlu2/3 agonists, a pharmacologically inactive peptidyl prodrug (L-alanine) form of the active compound LY354740, named LY544344, was developed. LY544344 is absorbed in the gastrointestinal tract through active PEP T1 transport, with eventual hydrolysis to produce molar equivalents of LY354740 and L-alanine (Bueno et al, 2005;Rorick-Kehn et al, 2006). In rodents, oral administration of LY544344 is associated with at least 10-fold improvement in bioavailability compared with oral LY354740 and behavioral effects comparable to those seen with parenteral administration of LY354740 (Rorick-Kehn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro data demonstrated that LY544344 is chemically stable but susceptible to hydrolytic enzymes in jejunal homogenates (Bueno et al, 2005). Previous reports demonstrated that this combination of active absorption and rapid enzymatic hydrolysis results in a dramatic increase in the oral bioavailability of LY354740 in rats (Rorick-Kehn et al, 2006) and humans (Kellner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the bioavailability and pharmacokinetic behavior of LY354740, a series of PepT1-targeted peptidyl prodrugs were evaluated using a series of in vitro and in vivo assays (Bueno et al, 2005). An N-linked alanyl prodrug, LY544344 (Fig.…”
mentioning
confidence: 99%
“…For example, a PET ligand for the mGlu 5 receptor has been developed, allowing a direct comparison of the level of receptor occupancy and distribution of mGlu 5 agonists or antagonists in animals and humans in vivo (Ametamey et al 2006Wyss et al 2007). The development of surrogate efficacy biomarkers has been more challenging, although the effects of the mGlu 2 agonist LY354740 in fear-potentiated startle in both animals and healthy volunteers have been described and can serve as an example for such an approach (Bueno et al 2005;Helton et al 1998;Johnson et al 2003;Tizzano et al 2002;Walker et al 2002). This and mGlu 5 -related PET ligand research will subsequently be described, followed by examples of studies in which direct comparisons are more difficult and a discussion of research in "translatable" paradigms that so far has been conducted in either humans or animals, but not both.…”
Section: Metabotropic Glutamate Receptors In Translationmentioning
confidence: 99%